Factors that influence teachers' decisions to use smartphone clicker apps to enhance teacher-student interactions in university classrooms in Saudi Arabia. (2nd January 2019) - Aljaloud, Abdulaziz; Billingsley, William; Kwan, Paul
ABSTRACT: Smartphone clicker apps are increasingly used in university classrooms to facilitate teacher–student interaction and collaborative learning. This study aimed to identify the factors that influence teachers' decisions to adopt smartphone clicker app technology to enhance teacher–student interactions in university classrooms in Saudi Arabia. A mixed-method study design was employed in this study. Thirty-three teachers from a Computer Science faculty completed a questionnaire and 14 of them participated in focus group interviews to provide their views. Two main findings emerged in this study: positive and significant relationships between teachers' perceptions of the smartphone clicker app's ease of use and its perceived usefulness; and a significant relationship between teachers' perceptions of the usefulness of the smartphone clicker app and their attitude towards its use in the classroom. This study also identified that training on how to implement the smartphone clicker app effectively in lesson activities is a significant influence on teachers' perceptions of the usefulness of, and their decision to use, the app. The main implication of these findings is that smartphone clicker app developers and user training coordinators must consider teachers' perceptions of the suitability of the technology and their desire to design learning tasks to facilitate student participation and engagement.